Association between CYP2C19 gene polymorphisms and lipid metabolism in Chinese patients with ischemic stroke. Issue 7 (July 2020) - Bai, Yunxue; Huang, Ruicheng; Wan, Lagen; Zhao, Rui
Objective: The CYP2C19 genetic variation may be involved in the development of atherosclerotic cardiovascular disease (ASCVD). Serum lipid levels are important risk factors for ASCVD, but the effect of the CYP2C19 gene on serum lipid metabolism remains unclear. This retrospective cohort study investigated the relationship between the CYP2C19 gene polymorphism and serum lipid levels in patients with ischemic stroke (IS). Methods: IS patients (n = 230) and control subjects (n = 100) were enrolled. All patients were diagnosed with IS via clinical manifestations and brain magnetic resonance imaging. All patients were genotyped. Results: Triglyceride (TG), total cholesterol (TC), low-density lipoprotein-cholesterol (LDL-c), and apolipoprotein B (ApoB) levels were significantly higher and high-density lipoprotein-cholesterol (HDL-c) and apolipoprotein A1 (ApoA1 ) levels were significantly lower in the IS group compared with the control group. Lower ApoA1 levels and higher ApoB levels were significant predictive factors for IS. Patients with higher ApoB levels had a higher risk of IS recurrence. Compared with extensive metabolizers, intermediate and poor CYP2C19 metabolizers had a higher risk of IS recurrence. Conclusions: Our study indicates CYP2C19 gene polymorphisms are related to lipid metabolism in patients with IS. IS patients who are poor CYP2C19 metabolizers may have a higher risk of disease recurrence.